Hiperglikemia Pada Terapi Nutrisi Parenteral - Dwi Anjani, Galuh; Junando, Mirza; Oktarlina, Rasmi Zakiah; Himayani, Rani (Medula, 2024)
Hyperglycemia is a condition that often occurs in some patients on parenteral nutrition therapy, both with and without a diagnosis of diabetes mellitus. The incidence of hyperglycemia is closely related to an increase in length of stay and mortality in hospital. This literature review aims to provide an overview of the management of hyperglycemia related to parenteral nutrition therapy. The source search method was carried out using the Google Scholar, Pubmed and Elsevier search engines. The keywords used are management of hyperglycemia, risk factors, parenteral nutrition. Based on the results of the literature review, it was found that several factors trigger the incidence of hyperglycemia, including BMI > 25 kg/m2, advanced age, higher HbA1c, history of type 2 DM, use of glucocorticoid drugs and administration of excess carbohydrates and reduced insulin sensitivity. Several strategies to prevent hyperglycemia are carried out by providing low dextrose, hypocaloric parenteral nutrition, or combining parenteral and enteral nutrition. Providing combined nutrition can improve glycemic control in patients with sufficient endogenous insulin stores. Meanwhile, therapeutic measures need to be given if hyperglycemia persists after preventative strategies are implemented. Therapeutic measures that can be taken include administering insulin intravenously or subcutaneously to patients in stable condition. Alternatively, insulin can be added to the parenteral nutrition mixture. It is important to closely monitor blood glucose levels to reduce the risk of hyperglycemia or hypoglycemia.